Effect of Corn Cob Addition on the Rheological and Filtration Properties of Water Based Drilling Mud - Apriandi Rizkina Rangga Wastu; Ridha husla; Ghanima Yasmianiar; Asri Nugrahanti; Venezia Chelsea Reggiana Kalalo; R Hari Karyadi Oetomo; Siti Azizah (Scientific Contributions Oil and Gas, 2026)
Drilling mud is an essential tool in supporting the success of productive and economical oil and gas well drilling activities. Some chemical additives used to enhance the physical and rheological properties of mud tend to be toxic, non-biodegradable, and have negative environmental impacts. The use of household waste materials such as corn cobs, which can be reused as a natural polymer in drilling mud, presents a promising alternative. The separation of these materials serves the purpose of identifying a new type of polymer candidate, as they contain 41.27% cellulose, 46% hemicellulose, and 7.40% lignin, making them suitable for use as a polymer. The research involves analyzing the mud rheology, including plastic viscosity, yield point, gel strength, filtration loss, and mud cake, using three samples of water-based mud containing 1.5 grams, 3 grams, and 4.5 grams of finely ground corn cobs. The samples are then tested at two different temperatures, 80ºF and 200ºF, to observe the behavior of corn cobs when circulated into the well and entering formations with higher temperatures. Changes in rheological values and filtration loss with each additive addition will serve as indicators of the feasibility of corn cobs as a biodegradable alternative additive containing cellulose in drilling mud.